2018
DOI: 10.1136/jramc-2017-000899
|View full text |Cite
|
Sign up to set email alerts
|

Association of betel nut chewing with exercise performance in a military male cohort: the CHIEF study

Abstract: Our findings suggest that the impairment of physical fitness associated with betel nut chewing of military young men might be mainly mediated or moderated by the coexisted cigarette smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
(16 reference statements)
2
20
0
Order By: Relevance
“…In addition, both short-duration sleep (≤5 h/day) and long-duration sleep (≥8 h/day) were associated with older adult BMI. This finding is consistent with a previous study that identified an association between sleep duration and BMI [18]. This reveals that older adults, especially women, who sleep less than 5 h or more than 8 h a day may have an increased risk of obesity [25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, both short-duration sleep (≤5 h/day) and long-duration sleep (≥8 h/day) were associated with older adult BMI. This finding is consistent with a previous study that identified an association between sleep duration and BMI [18]. This reveals that older adults, especially women, who sleep less than 5 h or more than 8 h a day may have an increased risk of obesity [25].…”
Section: Discussionsupporting
confidence: 93%
“…A face-to-face interview and physical examination were completed by a well-trained research assistant and nurses. The data from the questionnaire included demographic characteristics (i.e., age, sex, education, and monthly income), life habits (i.e., smoking, betel nut chewing (seed of areca palm, grows in the tropical Pacific and parts of east Africa, causes increased risk of diseases, and possibly impairs physical fitness [18]), and dieting), and health status. All data were recorded.…”
Section: Data Collectionmentioning
confidence: 99%
“…Blood biochemical tests for concentrations of triglycerides, total cholesterol, high-density lipoprotein, fasting glucose, and AST and ALT were enzymatically measured on an auto analyzer (AU640, Olympus, Kobe, Japan). All blood samples were collected by several experienced technicians at the same blood drawing station after an overnight 12-h fast for the participants [ 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…After the health examination, all participants took at least one of the three exercise tests including 2-min sit-ups, 2-mininute push-ups, and a 3000-m run at the Hualien Military Physical Training and Testing Center. The study design of CHIEF study has been described in detail previously [19,[21][22][23][24][25]. In 2014, there were 4080 participants receiving the health examination and exercise tests in the study.…”
Section: Study Populationmentioning
confidence: 99%